The state of response of autonomic nervous system in children with mitral valve prolapse - Mitiuriaeva-Korniyko, І.О.; Kuleshov, O.V.; Medrazhevska, Ya.A.; Fik, L.O.; Klets, T.D. (Medicni Perspektivi, 2021)
The article presents summarized materials on connective tissue dysplasia of the heart, primary mitral valve prolapse, dysfunction of the autonomic system. Aim of research: to estimate the condition of autonomic nervous system in children with primary mitral valve prolapse. We examined 106 children with mitral valve prolapse aged from 13 to 17 years old on the clinical base of city hospital “Center of mother and child” in Vinnitsya. Research included time and frequency domain (evaluation with cardiointervalography. Final results were compared with the control group records. The results showed no statistical significance among time domain parameters in the main group of children. All these indices displayed tendency to sympathetic and parasympathetic autonomic nervous system tonus increase in boys. However, sympathicotonia tendency was noted in girls only. Frequency domain parameters showed similar results, compared with the previous. Nevertheless, very low frequency parameters had statistically significant difference in both subgroups of patience with mitral valve prolapse, including males (3205.8±190.9 against 1717±154, р<0.05) and females (3280±220.1 against 1433±811, р<0.05). There were no statistically significant difference among other frequency domain parameters. Conclusions: we estimated that children with mitral valve prolapse have imbalanced autonomic homeostasis manifested by tone disturbances of both autonomic vegetative system branches with sympathetic predominance. Patients with primary mitral valve prolapse generally have increased sympathetic tone - both boys and girls - according to spectral analysis of heart rate variability indices, heart rate oscillation power of a very low frequency in particular (p<0.05). In children with mitral valve prolapse, the tone of parasympathetic nervous system is generally normal; there is a tendency to its increase in boys and decrease in girls. These children should be under close medical supervision by pediatricians and cardiologists.